The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Collaboration and competition in a children's health initiative coalition: A network analysis - Valente, Thomas W.; Coronges, Kathryn A.; Stevens, Gregory D.; Cousineau, Michael R. (Evaluation and Program Planning, 2008)
Activating communities to achieve public health change and initiate policy reform usually requires collective action from many entities. This case study analyzes inter-organizational networks among members of a coalition created to expand health insurance coverage to uninsured children in a large metropolitan area. Six networks were measured: collaboration, competition, formal agreements, receive funding from, send funding to, and greater communication. The response rate was 65.8% (50 of the 76 active members). Positive network questions such as “who do you collaborate with” elicited many network choices whereas negative ones such as “who do you compete with” elicited few. The collaboration network had a core–periphery structure and analysis showed that a large network can be reduced to a small set of core organizations one-sixth the size of the whole. Centrality (out- and in-degree) was associated with perceived organizational function and perceived barriers to success. For example, organizations that received many choices as collaboration partners were more likely to perceive the coalition functioned well than those who received few choices. The study suggests that perceptions of organizational performance are associated with position in the network, central members are more likely to perceive the organization performs well than those on the periphery.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; access to services / acesso a serviços; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

Health providers’ opinions on provider–client relations: results of a multi-country study to test Health Workers for Change - Fonn, S; Mtonga, AS; Nkoloma, HC; Bantebya Kyomuhendo, G; Dasilva, L; Kazilimani, E; Davis, S; Dia, R (Health Policy and Planning, 2001)
A multi-centre study in four African countries was undertaken to test the acceptability and effectiveness of Health Workers for Change, a methodology to explore provider–client relations within a gender-sensitive context. This intervention addresses the interpersonal component of quality of care. The methodology, consisting of six workshops, was implemented by research teams in Zambia, Senegal, Mozambique and Uganda. It was found to be acceptable within in a range of cultural and primary health care settings. The workshops allowed difficult issues such as prejudice and bribery to be discussed openly, fostered problem solving and the development of practical plans to address problems that could strengthen district health systems.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Accepted: 2016-02-01T14:49:31Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde